Tuning into the digital generation. The expansion of youth organizations to the platforms 2.0 - Martínez Rolán, Xabier; Piñeiro-Otero, Teresa (Historia y Comunicación Social, 2014)
The intense process of digitalizing of Spanish society has risen up the first generation of digital natives. This generation interacts with analogical subjects and structures, what reveals the existence of divergences between their communicative spheres. The adaptation of both spheres it’s a “must” for the institutions which develops youth policies, institutions that aim digital natives as their gold target. Present article it’s an approach to social media channels of regional institutions which develops youth policies - entities that communicates with that digital youth, in order to determine their relationship.